Field vs. Emergency Department Intubation: A Retrospective Review of Hospital Outcomes of Trauma Patients - Mitchell Vorce; Sagar Galwankar; Jarrod Shuck; Amit Agrawal (Western Journal of Emergency Medicine, 2025)
Introduction: Definitive airway management is crucial for severely injured trauma patients when basic pre-hospital interventions fail to provide adequate oxygenation and ventilation. Endotracheal intubation by emergency medical service (EMS) personnel is often necessary before reaching the emergency department (ED). While some studies suggest that advanced airway protocols in the pre-hospital setting improve survival in patients with severe head injuries, others indicate potential complications and adverse outcomes associated with pre-hospital intubation. In this study we aimed to evaluate whether trauma patients who underwent intubation by EMS in the field experienced different hospital outcomes compared to those intubated by physicians in the ED. Specifically, it assessed the impact of pre-hospital intubation on the number of days requiring mechanical ventilation, intensive care unit length of stay (ICU LOS), and overall hospital LOS. Methods: We conducted a retrospective chart review at a single, level II trauma center from January 1, 2019–December 31, 2023, involving trauma patients requiring intubation. Patients were divided into two groups: 608 patients ED department (ED ETT). Primary outcomes included days on mechanical ventilation, while secondary outcomes included ICU and hospital LOS. An independent t-test was performed to compare the differences in mean ventilator days, ICU LOS, and hospital LOS between the two groups, accepting P-value of <0.10 as significant. Results: The study included 1,010 patients, with a mean age of 55.5 years in the ED group and 52.5 years in the pre-hospital group. No statistically significant differences were found in mean ventilator days (4.1 ± 4.6 days for the ED group and 4.1 ± 5.7 days for the pre-hospital group), ICU LOS (5.8 ± 6.1 days in the ED ETT group vs 5.6 ± 7.4 days in the pre-hospital ETT group), or overall hospital LOS (10.1 ± 13.6 days in the ED group vs 10.2 ± 17.5 days in the pre-hospital group). Conclusion: These findings indicate no significant differences in patient outcomes between those intubated pre-hospital and those intubated in the ED. Further research is needed to make modifications to airway management protocols in the pre-hospital setting.